ГЕОДИНАМИЧЕСКАЯ ОБСТАНОВКА В НИЖНЕМ БЬЕФЕ КАМСКОЙ ГЭС (ПРАВОБЕРЕЖНАЯ ЧАСТЬ г. ПЕРМИ) (Географический вестник=Geographical bulletin, 2017)
Рассматриваются особенности переформирования береговой зоны нижнего бьефа Камского гидроузла в черте г. Перми. Приведена дифференциация ключевого участка берега по типу переформирования.GEODYNAMICS IN LOWER POOL OF THE KAMA HYDROELECTRIC POWER STATION (RIGHT BANK OF KAMA RIVER IN PERM)The differentiation of a coastal zone in lower pool of Kama hydroelectric power station in Perm city was organized as a rearrangement. As a result, the following types of coast have been allocated: abrasion-erosion-collapse, abrasion-erosion-landslide, abrasion-erosion-gully, coast break off of a slope, coast hydration aerations and phytogenous destruction, residential coast with handicraft coast protection constructions, artificial beaches, technogenic coast.